2013
DOI: 10.1002/cbic.201300229
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Radiolysis Studies on the Reaction of the Reduced Vitamin B12 Complex Cob(II)alamin with Superoxide

Abstract: O2.− scavenger: The rate constant for the rapid reaction of the ROS superoxide with the reduced vitamin B12 radical complex cob(II)alamin was directly determined to be 3.8×108 M−1 s−1. This rate was independent of pH over the range 5.5–8.7. These results have implications for studying the use of B12 supplements to combat diseases associated with oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Cobalamin(II) has been shown to react with O 2 · − at a rate two times faster than we found for Cbi(II) [( 13 ) and Table 1 ], but to our knowledge, the reaction of cobalamin(III) with O 2 · − has not been reported. We found that cobalamin(III) reacts with O 2 · − , but at a rate less than one-tenth that of Cbi(III) (Figure S1C, D, Table 1 ).…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…Cobalamin(II) has been shown to react with O 2 · − at a rate two times faster than we found for Cbi(II) [( 13 ) and Table 1 ], but to our knowledge, the reaction of cobalamin(III) with O 2 · − has not been reported. We found that cobalamin(III) reacts with O 2 · − , but at a rate less than one-tenth that of Cbi(III) (Figure S1C, D, Table 1 ).…”
Section: Resultscontrasting
confidence: 47%
“…We wanted to compare cobinamide to similar agents, and chose cobalamin, imisopasem, and MnTBAP for the following reasons. Cobalamin is structurally similar to cobinamide, cobalamin(II) reacts readily with O 2 · − and ONOO − , both cobalamin(II) and cobalamin(III) react with hydrogen peroxide, and cobalamin has antioxidant effects in several in-vivo systems [Table 1 ; ( 13 , 14 , 17 , 19–21 )]. Imisopasem and MnTBAP are SOD mimetics, with imisopasem having a relatively high reaction rate with O 2 · − , and MnTBAP additionally reacts with ONOO − ; both agents have been used extensively in cells and animals ( 24–32 ) (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central cobalt can change its oxidation state between +3 (cob(III)alamin), +2 (cob(II)alamin), and +1(cob(I)alamin), which makes these compounds redox active. Moreover, it has been shown that Cbl reacts with O 2 •− at rates comparable with that of superoxide dismutase [ 79 , 80 ]. Hence, it has been suggested that cobalamins modulate inflammation and redox status [ 81 83 ] in addition to and independently of their cofactor function.…”
Section: Micronutrientsmentioning
confidence: 99%
“…[3, 14a,c,d] Vitamin B 12 derivatives, also knowna sc obalamins (Cbls), Figure 1, are essential cofactors for mammalian methionine synthasea nd mitochondrial methylmalonyl-CoA mutase. [15] Like porphyrins, the metal center of reduced cobalaminsisr apidly oxidized by ROS/RNS, including superoxide, [16,17] nitric oxide, [18] peroxynitrite, [19] nitrogen dioxide, [20] and nitrite. [21] Furthermore ROS such as NO inactivate methionine synthase and methylmalonyl-CoA mutase.…”
Section: Introductionmentioning
confidence: 99%